Exploring a Paradigm Shift in Primary Teeth Root Canal Preparation: An Ex Vivo Micro-CT Study - Dora Schachter; Sigalit Blumer; Sara Sarsur; Benjamin Peretz; Tatiana Sella Tunis; Shada Fadela; Johnny Kharouba; Shlomo Elbahary (MDPI AG, 2023)
Traditional hand instrumentation is a commonly used technique to perform pulpectomy in deciduous teeth by most specialists in pedodontics. Lately, dentists have embraced rotary instrumentation as a safe and effective alternative. This study aimed to compare the efficacy of root canal preparation in extracted primary molars between manual and two rotary file systems using micro-CT. Thirty-six extracted human second primary mandibular molars were divided into three groups according to the instrumentation method: (1) Manually instrumented (MI) group (n = 9) in which the teeth were treated using K-files up to size 30; (2) Kedo-Ssystem (KS) group (n = 9); (3) ProTaper Gold system (PTG) group (n = 10) and control group (n-8). Each tooth was scanned before and after the retrograde root canal preparation. Residual dentin volume was calculated using micro-CT scans to evaluate the technique's efficacy. Additionally, the preparation time and procedural errors were recorded for each tooth preparation. A one-way ANOVA test was carried out to compare the groups' dentin volume and preparation time. The mean preparation time using the manual method (13.14 min) was more than two times longer than that of the rotary techniques (4.62 min and 6.45 min). The manual preparation method using a K-file removed almost half the root canal material when compared with the rotor method (p = 0.025). Conclusion: our results suggest that rotary instrumentation is more efficient for root canal preparation in primary teeth than the traditional manual method. This finding may call for a paradigm shift in current clinical practices, where manual instrumentation is still commonly preferred.